Developing a framework to nurture supporting environments that will encourage growth amongst impoverished youth - Ibrahim, Rahinah; Kamarudin, Anna Kamelia (Zes Rokman Resources, 2024)
Educators need to understand the impoverished youth's education, skills, capabilities, behavioral and social sciences to effectively prepare them for livelihood. The purpose of this study is to tackle interdisciplinary perspectives on how to analyze the key factors in a supporting environment that will encourage growth amongst impoverished youth. This study uses literature review to analyze the factors that define impoverished youth, to evaluate the best environmental sociology that encourage their growth in order to have a meaningful life and to identify the advancement of the humanities in order to develop a framework to nurture a supporting environment that will encourage their growth. Results of the study includes definition of impoverished youth, their socio-cultural characteristics, recommended best encouragement growth programs, best practices and evidence-based approach, strategies in creating a supportive environment and theory on the impact of a supportive environment towards encouraging growth. The results are expected to lead towards an emerging area of thinking of understanding Impoverished youth and their socio-cultural characteristics variables.The grand societal challenge allows studies to recommend programs, propose best practices and evidence based approaches, propose strategic procedures in creating a supportive environment and theory on the impact of a supportive environment towards impoverished youth motivation. This study is proposing that social entrepreneurship could nurture impoverished youth to develop leadership skills through a growth leadership program, conducted in a safe learning environment that considers their character, psychological behavior and cultural context. The significance of this study lies in its potential to drive meaningful change in how we approach youth empowerment, particularly in impoverished communities. By comprehensively understanding the various factors that influence the lives of impoverished youth, including their character, psychological behavior, neighborhood environment, and cultural influences, the study provides a foundation for developing targeted interventions that address their specific needs and challenges.Future studies in this area could delve deeper into the lived experiences of impoverished youth participating in empowerment programs through qualitative research methods such as interviews, focus groups, and participant observation. This would allow for a nuanced understanding of the factors that facilitate or hinder their empowerment journey.